Zoneamento agroclimático da cultura da cana-de-açúcar na América do Sul em função das projeções do modelo climático global ECHAM5_MPI-OM - Pimenta, Luciano Roncete (2012)
The Intergovernmental Panel on Climate Change - IPCC has been alert that the global warming is unequivocal. It is evidenced an elevation of about 0,2 °C in global temperature over the last 30 years. The results presented in the Fourth Assessment Report on